Earthquake Insurance in Turkey : History of the Turkish Catastrophe Insurance Pool - Gurenko, Eugene; Lester, Rodney; Mahul, Olivier; Gonulal, Serap Oguz (Washington, DC: World Bank, 2012)
This publication, Earthquake insurance in Turkey, is an exposition of the dangers faced by Turkey as it is located in one of the most active earthquake (EQ) and volcanic regions in the world on the one hand, and, on the other hand, the efforts that Turkey is making to alleviate the social and fiscal disasters that are caused when these calamities do strike. The persistent potential for large-scale disasters has led to the establishment of the Turkish Catastrophe Insurance Pool (TCIP) in 1999. The main rationale for the creation of TCIP was a very low level of catastrophe insurance penetration among households. The authors stress that the four principal objectives of the program are to (1) provide earthquake insurance coverage at affordable but actuarially sound rates for all registered urban dwellings, (2) limit the government's financial exposure to natural disasters, (3) build long-term catastrophe reserves to finance future earthquake losses, and (4) encourage risk reduction and mitigation practices in residential construction. The book points out that the program has reduced significantly the government's fiscal exposure to EQ risk. In five years, the TCIP transformed itself from an unknown and controversial government-sponsored program to one of the most trusted brand names in the Turkish insurance industry. Moreover, it has led the World Bank to rethink the roles of ex-ante risk management relative to ex-post donor support. In this context, the World Bank supported Turkey's earthquake insurance program to establish and expand national catastrophic risk management and risk transfer capabilities. The authors conclude that the TCIP's success has brought it worldwide recognition. Inspired by the TCIP's example, more than a dozen countries, including China, Colombia, Greece, India, the Islamic Republic of Iran, Italy, the Philippines, Romania, and nine island states of the Caribbean have begun technical and legislative preparation of catastrophe insurance programs.